2019
DOI: 10.1016/j.tsf.2018.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Development of reflective back contacts for high-efficiency ultrathin Cu(In,Ga)Se2 solar cells

Abstract: Because of poor light absorption, Cu(In,Ga)Se2-based (CIGS) solar cells with an ultrathin absorber layer (<500 nm) require the development of reflective back contacts. To enhance rear reflectance in CIGS ultrathin devices, we investigate novel back contact architectures based on a silver metallic mirror covered with a thin layer of In2O3:Sn (ITO), which is fully compatible with nanopatterning for further light trapping improvements. First, numerical electromagnetic simulations of complete solar cells have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Besides, the annealing of the RBC resulted in a significant enhancement of the RBC reflectivity for wavelengths above 600 nm. This improvement may be attributed to a modification of ITO optical indices upon annealing, as determined by ellipsometry in a previous study 30 . The annealed RBC reaches an average reflectance of 92.6% for wavelengths above 500 nm.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Besides, the annealing of the RBC resulted in a significant enhancement of the RBC reflectivity for wavelengths above 600 nm. This improvement may be attributed to a modification of ITO optical indices upon annealing, as determined by ellipsometry in a previous study 30 . The annealed RBC reaches an average reflectance of 92.6% for wavelengths above 500 nm.…”
Section: Resultssupporting
confidence: 53%
“…The optical indices of CIGS were first determined by ellipsometry 34 and subsequently refined close to the bandgap thanks to photocurrent Fourier‐transform spectroscopy measurements, and the thickness of the simulated CIGS layers was fixed at its experimental average value of 510 nm. The optical indices of ITO were also derived from ellipsometry data described in a previous study 30 . More information about this optical model and the optical simulations performed in this study can be found in reference Goffard et al 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] Recently, ref. [15] showed an experimental gain in short‐circuit current density of 4.9 mA cm − 2 in a structure Mo/Ag/ITO/0.5 μm CIGSe with respect to the reference structure of Mo/0.5 μm CIGSe. Al/ITO‐based solar cells can be prepared up to at least 600 °C without Al diffusion inside the absorber while providing high reflectivity at long optical wavelengths.…”
Section: Introductionmentioning
confidence: 91%
“…To minimize this effect thin Ag layer under these openings can be etched away and Mo takes the role of the local contact point. An alternative to prevent Ag diffusion into CIGS is to use TCO layer as Ag cover [18]. TCO layers (e.g.…”
Section: Device Structure and Texturesmentioning
confidence: 99%